Monopsony power and labor income inequality in Mexico - Chiara Cazzuffi; Mariana Pereira-López; Irving Rosales; Isidro Soloaga (Inter-American Development Bank (IDB), 2023)
We examine the impact of changes in local labor market concentration on two components of income inequality in Mexico: local wage shares and labor income inequality. Combining data from the Economic Census and the Population and Housing Censuses, we analyze the mechanisms that drive the relationship between concentration and labor income inequality by considering heterogeneities across groups of workers (skilled and unskilled) and sectors. In line with previous studies for developed countries and with the emerging literature on monopsony power, we first show that a higher level of concentration is associated with reductions in skilled and unskilled workers' wages. Furthermore, the elasticities are relatively similar. Second, there is sectoral heterogeneity as, for manufacturing, unskilled workers' wages decrease more, while skilled workers do not exhibit any reduction. On the other hand, for services, the effects are similar for the two groups. Third, unionization plays a countervailing role against monopsony power, as in highly-unionized sectors, the effect of higher concentration on wages is null, and this is consistent with a higher level of bargaining power. Even though the effects of labor market concentration on inequality are not sizeable, the impact on wages for skilled and unskilled workers is significant.
Keywords: J23; J31; J42; 330; Inequality; Monopsony; Labor markets